Tracking a target moving in a known road network by square-root equality-constrained filtering - Chisci, L.; Mavino, A.; Papi, Francesco; Perferi, G.; Benavoli, A.; Farina, A. (2008)
In this paper, a square-root equality-constrained linear filter is used to track a target moving along a road. This choice provides a computationally efficient, algorithmically simple and numerically robust solution for the implementation of a VS-DMM (Variable Structure - Dynamic Multiple Model) filter. A performance evaluation via Monte Carlo simulations shows the effectiveness of the proposed approach. © 2008 IEEE.